PENGARUH STORE ATMOSPHERE DAN INFLUENCER MARKETING TERHADAP BRAND AWARENESS DAN KEPUTUSAN PEMBELIAN STREET BOBA DI KOTA PEKANBARU - ,Tengku Firli Musfar, Ningsi Oktavia Sari ,Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
ABSTRACTThis study aims to analyze the effect of the Store Store atmosphere and influencer marketing on brand awareness and purchasing decisions. The population in this study are all consumers who have purchased Street Boba brand beverage products in the city of Pekanbaru whose numbers are unknown with certainty. Primary data in this study was obtained from the distribution of questionnaires as an instrument to prove the results of the research or hypothesis submitted. The sample used amounted to 120 respondents, determining the sample using a non -probability sampling technique with the accidental sampling procedure. This research is a quantitative descriptive research that uses a path analysis data processing method with the help of SPSS (Statistical Package of Social Science) version 23. The results of the study showed that, Store Atmosphere and Influencer Marketing had a positive and significant effect on brand awareness. Store atmosphere and influencer marketing has a positive and significant effect on purchasing decisions. Store atmosphere and influencer marketing has a positive and significant effect on purchasing decisions through brand awareness.Keywords: Store Atmosphere, Influencer Marketing, Brand Awareness, Purchase Decisions